2022
DOI: 10.1038/s41467-022-32266-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis defines highly refractory RAS burdened immature subgroup of infant acute lymphoblastic leukemia

Abstract: KMT2A-rearranged infant acute lymphoblastic leukemia (ALL) represents the most refractory type of childhood leukemia. To uncover the molecular heterogeneity of this disease, we perform RNA sequencing, methylation array analysis, whole exome and targeted deep sequencing on 84 infants with KMT2A-rearranged leukemia. Our multi-omics clustering followed by single-sample and single-cell inference of hematopoietic differentiation establishes five robust integrative clusters (ICs) with different master transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…The lineage identities and therapeutic responses of KMT2A r leukemias are highly heterogeneous 1,5,7,8 . To characterize the molecular basis of this heterogeneity we applied Automated CUT&RUN to profile the oncoprotein binding sites across 34 KMT2A r leukemia samples that span the age of onset and are representative of the diverse mutations and lineage subtypes that are observed in KMT2A r leukemias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lineage identities and therapeutic responses of KMT2A r leukemias are highly heterogeneous 1,5,7,8 . To characterize the molecular basis of this heterogeneity we applied Automated CUT&RUN to profile the oncoprotein binding sites across 34 KMT2A r leukemia samples that span the age of onset and are representative of the diverse mutations and lineage subtypes that are observed in KMT2A r leukemias.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in targeted immuno-therapies and pharmacological inhibitors have dramatically improved the treatment options for KMT2A r leukemias 5,6 . Despite sharing genetically related oncogenic lesions, KMT2A r leukemias show highly heterogeneous responses to therapeutic intervention 5,7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that pediatric tumours are often stalled in their developmental programs related to their cell of origin, which could be translated to a developmental program specific sgRNA library to use in pediatric tumour models. 91,96 In particular for transductions of tumour source material or intricate organoid model systems, where cell numbers are often limited, a smaller sgRNA library would be of great benefit to study genetic dependencies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these classi cations, the differential gene expression was calculated using the Seurat tool 'FindMarkers' using DESeq2 as the 'test.use' 56 . This methodology has been found to accurately identify differentially expressed genes in comparison with alternative exploratory tools and been used in multiple other exploratory studies of differential gene expression [57][58][59] . An average Log2 (fold change) >1 and an adjusted p value <0.05 were considered the cut-off criteria for differentially expressed genes.…”
Section: Single Cell Quality Control and Processingmentioning
confidence: 99%